2005
DOI: 10.1172/jci25365
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis modulates protective immunity to the pathogenic fungus Histoplasma capsulatum

Abstract: Pathogen-induced apoptosis of lymphocytes is associated with increased susceptibility to infection. In this study, we determined whether apoptosis influenced host resistance to the fungus Histoplasma capsulatum. The level of apoptotic leukocytes progressively increased in the lungs of naive and immune mice during the course of H. capsulatum infection. T cells constituted the dominant apoptotic population. Apoptosis was diminished in H. capsulatum-infected gld/gld and TNF-α-deficient mice; concomitantly, the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 71 publications
(57 reference statements)
3
44
0
Order By: Relevance
“…Others have suggested that Histoplasma-induced T cell apoptosis is a requirement for developing effective antifungal protection (38). Microscopic examination of Histoplasma-infected liver granulomas by H&E staining did not show frequent central necrosis in C57BL/6 mice.…”
Section: Apoptosis Of Granuloma-infiltrating Leukocytes In Histoplasmmentioning
confidence: 81%
See 1 more Smart Citation
“…Others have suggested that Histoplasma-induced T cell apoptosis is a requirement for developing effective antifungal protection (38). Microscopic examination of Histoplasma-infected liver granulomas by H&E staining did not show frequent central necrosis in C57BL/6 mice.…”
Section: Apoptosis Of Granuloma-infiltrating Leukocytes In Histoplasmmentioning
confidence: 81%
“…It may also be important in the control of the yeast by clearing infected cells. An intriguing report (38) shows that apoptosis is a prerequisite for a successful immune response. Mycobacteria are also known to evade immune clearance by inhibiting apoptosis in the infected macrophage (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Boc-D-FMK (pan-caspase inhibitor; SigmaAldrich) (0.2 mol) or Z-FA-FMK (control peptide; Sigma-Aldrich) (0.2 mol) was dissolved in 10 l of dimethyl sulfoxide (DMSO) for storage and diluted with 190 l of sterilized Dulbecco's PBS immediately before injection. Mice were injected intraperitoneally with Boc-D-FMK or Z-FA-FMK at the time of intratracheal infection with Histoplasma and daily afterwards until the day of the experiment (2).…”
Section: T Cell Activation Taken Together Our Results Revealed Thatmentioning
confidence: 99%
“…The cell pellet was collected by centrifugation (450 ϫ g, 5 min, 4ЊC) and resuspended in HBSS. The lymphocyte population was then isolated using a 40-70% Percoll (Pharmacia, Uppsala, Sweden) gradient (23). Cells were incubated with allophyocyanin (APC) or fluorescein isothiocyanate-conjugated antibodies (1 g antibody per 20 l staining buffer) and isotype controls.…”
Section: Evaluation Of Airway and Tissue Cellular Recruitmentmentioning
confidence: 99%